2003
DOI: 10.2136/sssaj2003.1616
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Applicability of Laser‐Induced Breakdown Spectroscopy for Total Soil Carbon Measurement

Abstract: ABSTRACTchanges in land use or disturbances such as fire or drought and the associated increases in erosion that can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 8 publications
1
77
0
4
Order By: Relevance
“…However, the utilization of an internal standard and other alternative calibration methods has ameliorated this matter. Water [217][218][219][220][221][222] and soil [223][224][225][226][227][228][229][230][231][232][233] analyses have produced most of the papers found in the literature.…”
Section: Environmental Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the utilization of an internal standard and other alternative calibration methods has ameliorated this matter. Water [217][218][219][220][221][222] and soil [223][224][225][226][227][228][229][230][231][232][233] analyses have produced most of the papers found in the literature.…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…In addition, LIBS was employed to determine metal contaminants in freshwater invertebrates. 229 Cremers et al 230,231 measured total soil carbon by LIBS. The sample was placed in a small quartz tube (25 mm diameter, 75 mm long) and the laser beam was focused onto the center of the tube.…”
Section: Environmental Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are near-infrared spectroscopy (NIR) [Sudduth and Hummel 1996;Christy et al, 2003], laser-induced breakdown spectroscopy (LIBS) [Ebinger et al, 2003], and inelastic neutron scattering (INS) [Wielopolski, 2006], the last one being the subject of the present chapter. These three techniques respectively entail spectroscopy on the molecular-, atomic-, and nuclear-levels.…”
Section: In Situ New Modalitiesmentioning
confidence: 99%
“…The Reports that use LIBS for measuring soil organic C generally use large benchtop instruments with prepared samples and calibrations to predict soil organic C from the measured elemental C (Bel'kov et al, 2008;Cremers et al, 2001;Ebinger et al, 2003;Knadel et al, 2017). These studies reported good correlations between LIBS measurements and those from dry combustion, particularly for soil with similar morphology (Cremers et al, 2001;Ebinger et al, 2003).…”
Section: Laser Induced Breakdown Spectroscopy (Libs)mentioning
confidence: 99%